Анализ электромагнитных процессов в индукторной системе – инструменте рихтовки автомобильных кузовов - Батыгин, Ю.В.; Чаплыгин, Е.А.; Шиндерук, С.А. (Електротехніка і електромеханіка, 2015)
С привлечением расчетных зависимостей для плотности индуцированных токов и распределенной силы притяжения
проведен анализ процессов в экспериментальных моделях индукторной системы с притягивающим экраном и
внешним дополнительным витком. Дана численная оценка влияния дополнительных витков на пространственновременные распределения основных характеристик электромагнитных процессов. Із залученням розрахункових залежностей для щільності індукованих струмів і розподіленої сили тяжіння проведено
аналіз процесів в експериментальних моделях індукторної системи з притягуючим екраном і зовнішнім додатковим
витком. Дана чисельна оцінка впливу додаткових витків на просторово-часові розподіли основних характеристик
електромагнітних процесів. Introduction. One of the promising directions of
electromagnetic forming (EMF) is a contactless magnetic-pulse
straightening of the automobile bodies. The efficiency and the
quality of the straightening depend on design and operating
principle of the straightening tool. In the modern technique of
EMF a large number of the tools - inductor systems (IS) is used
in different configurations with uneven distribution forces on the
treatment object that in turn does not meet the needs of the
effective process of straightening. There appears the urgent
necessity to create IS with high uniformity of the induced field
and a high concentration of attracting forces in the working
area of the tool. The most effective IS are the Inductor Systems
with an Attracting Screen (ISAS). One of the most important
considerations when choosing a particular design ISAS is the
study of the electrodynamics processes with definition of excited
loads. The nature and the course of the electrodynamics
processes in accordance with design features determine the
effectiveness and the efficiency of the ISAS. Therefore, in ISAS
an additional coil for the concentration of the attracting forces
in the working area should be entered. Purpose. The numerical
analysis of the induced fields and the currents in the
experimental models of ISAS with an additional coil was made.
Methodology. In the idealization of the «extremely low»
frequencies of existing fields, there were received rated
dependences for density of the induced currents and distributed
attracting force in ISAS and the external additional coil,
through the use of the calculated model in the cylindrical
coordinate system. Results. Insertion of the additional coil
placed over the accessory screen allows to concentrate and
increase the amplitude of the attracting forces in the central
part of the working area of the inductor system. Practical value.
1. Numerical analysis of fields and currents in experimental
models of Induction Systems with Attracting Screen (ISAS) and
additional coil, designed to align the metal coatings of vehicles
was made. 2. It is shown that if in ISAS they insert additional
coil placed over the accessory screen significantly increases the
amplitude of excited forces of attraction. 3. It is shown that the
parallel connection of the primary and additional coils in ISAS
allows to concentrate the forces of attraction in the centre of the
working area of the tool for straightening automobile bodies.